KARAKTERISASI BIODEGRADABLE FOAM DARI LIMBAH KULIT SINGKONG MENGGUNAKAN PENDEKATAN METODE BIOKATALIS - Kurniawan, Dodi; Rezki, Amelia Sri; Wulandari, Yeni Ria; Variyana, Yeni; Silmi, Fadian Farisan (Indonesian Journal of Pure and Applied Chemistry, 2025)
Biodegradable foam made from natural starch offers a sustainable alternative to Styrofoam, which is lightweight, low-cost, but challenging to degrade and harmful to the environment. The purpose of this study is to utilize cassava peel waste, which contains starch, as a raw material for producing biodegradable foam using a biocatalyst method approach, thereby reducing the presence of cyanide acid in cassava peel waste. Aside from that, Carboxy Methyl Cellulose (CMC) is used as a filler to strengthen the structure of biodegradable foam with mass variations of 4, 6, and 8 g. The characteristic cassava peel flour results showed that the biocatalyst method, achieved through fermentation, can reduce cyanide acid levels in cassava peel flour. Then, a biodegradable foam with the best characteristics was produced by adding 6 g of CMC, resulting in a thickness of 1.9 mm, a water absorption capacity of 17.45%, a tensile strength of 3.13 MPa, and a biodegradation level of 100%. The resulting biodegradable material exhibits a tensile strength that exceeds that of Styrofoam and can disintegrate completely in the soil.